Evaluasi Implementasi Kebijakan Penanggulangan Bencana Tanah Longsor oleh BPBD Kota Padang di Lubuk Begalung - Regina, Putri; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This research aims to evaluate the landslide disaster management policy in Lubuk Begalung implemented by the Regional Disaster Management Agency (BPBD) of Padang City. This research used a qualitative method with a descriptive approach, which was conducted at the BPBD office in Padang City. Informants in this study were selected using a purposive sampling technique. Data were collected through observation, interviews, and documentation. The results showed that the evaluation of the landslide disaster management policy by BPBD Padang City in Lubuk Begalung focused on the policy's effectiveness, efficiency, adequacy, and equity.